FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUASAN KERJA KARYAWAN RUMAH SAKIT MATA PBEC - B. Isyandi; Agus Taufiq; Trio Saputra; Prihati Prihati (Universitas Lancang Kuning, 2022)
This study aims to analyze the factors that affect employee job satisfaction at PBEC Eye Hospital. The data of this study consisted of primary and secondary data, which were taken through a questionnaire to 81 employees of the PBEC Eye Hospital with a sample census. The variables used are psychological factors, social factors, physical factors, and financial factors as independent variables and job satisfaction as the dependent variable. The data obtained were processed using SmartPLS. The results of this study indicate that psychological factors, social factors, and physical factors have a positive and significant effect on employee job satisfaction. And financial factors have no significant effect on employee job satisfaction